Genetic analysis of agro-morphological traits in promising hybrids of sunflower (Helianthus annuus L.) - Maryam GOLABADI; Pooran GOLKAR; Mohammad Reza SHAHSAVARI (Acta Agriculturae Slovenica)
The main objective underlying sunflower breeding programs is to develop high-yielding productive F1 hybrid cultivars. This study was conducted to investigate the genetic control of some agro-morphological traits of new sunflower F1 hybrids. For this purpose, fourteen inbred lines of sunflower were crossed with three male sterile inbred lines. Their hybrids (14 hybrids) were then evaluated against three control cultivars. The data thus obtained were analyzed using the nested model (North Carolina Design І) as a completely randomized block design (CRBD) with four replications. Analysis of variance showed that the hybrids were significantly different in all the traits studied, except for head and stem diameters. From among the hybrids evaluated, Cms19 × Rn1-81 was found to have the highest seed yield and oil content. Cluster analysis classified the hybrids into four different groups. Genetic analysis showed that days to maturity, seed weight, and oil content (%) were under the additive gene action. Breeding strategies based on selection could be suggested for the improvement of these traits. Head angle, head diameter, seed yield, and oil yield were under the dominance gene action; breeding based on hybridization methods is, therefore, proposed for these traits. Finally, both additive and dominance gene actions were observed to play important roles in the genetic control of plant height and stem diameter.